Analisis Faktor-Faktor Stressor Terhadap Streskerja Dan Kinerja Karyawan Kementerian Keuangan - Ami Pujiwati; Etty Susanty (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
The purpose of this study was to determine the factors that become a stressor to stress the work and employee performance and to determine the effect of work stress on employee performance Secretariat General of the Ministry of Finance. This research was conducted on the employee group III at 5 (five) units which are under Sekretariatan General of the Ministry of Finance of the Republic of Indonesia. The analytical method used path analysis using SEM analysis tools SmartPLS. The sample used in the study amounted to 150 respondents. The results showed that the lack of authority in order to carry out the responsibilities of being a major factor in generating stress (stressors) whereas the difficulty to get along with superiors, they cause work stress. While taking risks and thinking hard to always be able to work with either a major factor in improving employee performance. Stressor in the office of the Secretary General of the Ministry of Finance significantly positive effect on employee stress, while in the office of the Secretary General of the Ministry of Finance stressor does not significantly affect the employee performance and job stress did not significantly affect performance.